The Utility of Point- of- Care-Ultrasound in Primary Care (Global Journal of Medical Research, 2023)
The antecedent of ultrasound goes back to the 1940s after World War II when the prospect of ultrasound in medical practices was developed In 1951 1 the workshop of Douglas Howry a radiologist and his collaborators Bliss and Posakony make possible the creation of a two-dimensional ultrasound scanner Since also ultrasound has elaborated over the occasions to approach a really useful tool in clinical radiology 2 The denomination of ultrasound at the point of care Point of Care Ultrasound POCUS remodeled the paradigm of the ultrasound test carried out by imaging specialists or cardiologists defined by the descriptive pattern of the organs and carried out in certain time and places to turn an extension of the physical examination examination palpation percussion auscultation and insonation 3 Multiorgan clinical ultrasound must be achieved by the attending physician in any care setting from home to an intensive care unit or operating room
Keywords: general practice; family medicine; primary care; point-of-care testing; ultrasonography echography